BERHENTI MENUNDUK, MULAI BERBICARA: SOSIALISASI DAMPAK PHUBBING DI ERA DIGITAL: BERHENTI MENUNDUK, MULAI BERBICARA: SOSIALISASI DAMPAK PHUBBING DI ERA DIGITAL - Abdullah Mitrin; Rudi Rahman; Risa Amalia (LPPM Universitas Awal Bros, 2026)
The digital era has brought significant changes in social communication patterns but also presents challenges such as phubbing the behavior of ignoring direct social interactions due to excessive focus on digital devices. In Tebing Tinggi Okura Village, 75% of the population, particularly those aged 15-35, frequently experience or witness phubbing, which negatively impacts communication quality, increases anxiety, and fosters feelings of loneliness. Therefore, education and socialization are essential steps to address this issue. This Community Service Program aims to enhance public awareness of the negative impacts of phubbing and provide practical strategies to reduce this behavior, promoting healthier social interactions. Through seminars, workshops, and digital campaigns, public awareness increased by up to 70%, with educational methods such as interactive discussions and educational videos proving effective in engaging participants. Additionally, social media campaigns reached over 10,000 interactions. Pre-test and post-test evaluations showed an increase in participants' understanding from 30% to 70%, serving as a foundation for follow-up actions, including integrating the material into school curricula and training teachers and community leaders.